ANALISIS SEMIOTIKA RIFFATERRE PADA HAIKU MUSIM PANAS DALAM BUKU OKU NO HOSOMICHI KARYA MATSUO BASHO - Rahmad Novianto Ardiansyah (SUAR BETANG, 2017)
Haiku is a literary kind of poetry that originated in Japan. Haiku initially have three major streams namely Teimon, Danrin, and Basho. Haiku has rules in writing that is using the 5-7-5 syllable construction, using kireji, and Kigo included therein. This study will use ten haiku of Matsuo Basho summer work in the book Oku no Hosomichi drawn randomly. This study uses structural semiotics, a method that examines the content of literature and semiotic approach. The semiotic approach used here is Riffaterre semiotic, namely heuristic reading, hermeneutic reading, matrices seeking, models, and variants, as well as the hipogram. The results of this study are the meaning of ten haiku is Basho sense of awe, gratitude, joy, serenity, solitude and sadness